EFEKTIVITAS ELEVASI EKSTREMITAS BAWAH TERHADAP PROSES PENYEMBUHAN ULKUS DIABETIK DI RUANG MELATI I RSUD DR. MOEWARDI TAHUN 2014 - Dwi Ariani Sulistyowati (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstractIntroduction: People with Diabetes Mellitus have poor circulation, especially in areas far from heart, these causing the length of time of wounds healing. One of the interventions to improve the peripheral tissue perfusion of patients with Diabetic Ulcer is lower extremity elevation.Purpose: The purpose of this research is describe the characteristics of respondents, knowing Diabetic Ulcer healing process without lower extremity elevation, knowing Diabetic Ulcer healing process with lower extremity elevation and knowing the effectiveness of Diabetic Ulcer healing without lower extremity elevation and with lower extremity elevation.Research Methods: This research is to design an quasy experiment non equivalent control group design and analysis data used Independent T TestResearch Results: Results of this research is the elevation of lower extremities more effectively to increased Ulcers Diabetic healing process. It’s evidenced by Independent T Test obtained p = 0,000Conclusion: Elevation of lower extremities more effectively to increased Diabetic Ulcer healing in patients with Diabetic Ulcer in Melati I RSUD Dr. Moewardi.Advice: Lower extremity elevation expect can be applied in patients with Diabetic Ulcer.Key Words: Lower Extremity Elevation, Diabetic Ulcer Healing Process